2009
DOI: 10.1016/j.neuron.2009.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Immune Influence on Adult Neural Stem Cell Regulation and Function

Abstract: Neural stem cells (NSCs) lie at the heart of central nervous system development and repair, and deficiency or dysregulation of NSCs or their progeny can have significant consequences at any stage of life. Immune signaling is emerging as one of the influential variables that define resident NSC behavior. Perturbations in local immune signaling accompany virtually every injury or disease state and signaling cascades that mediate immune activation, resolution, or chronic persistence influence resident stem and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
180
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(185 citation statements)
references
References 153 publications
(229 reference statements)
2
180
0
2
Order By: Relevance
“…TNF-a receptor expression in this hNSC population, or developmental regulation of TNFR1/2 expression in neural stem versus progenitor cells (82). Future studies will further investigate the possible signaling mechanisms mediating the specific effect of complement-mediated astrogliogenesis in hNSC.…”
Section: Discussionmentioning
confidence: 92%
“…TNF-a receptor expression in this hNSC population, or developmental regulation of TNFR1/2 expression in neural stem versus progenitor cells (82). Future studies will further investigate the possible signaling mechanisms mediating the specific effect of complement-mediated astrogliogenesis in hNSC.…”
Section: Discussionmentioning
confidence: 92%
“…This would be due to the apoptotic and necrotic cell death 17 . Although these cell deaths could be caused by immune rejection 18 , significant T-cell infiltration, which is an indicator of immune rejection, was not observed at the initial and late phase after transplantation (Supplementary Fig. S2).…”
Section: Cell Viability and Functional Improvementmentioning
confidence: 99%
“…[43] In the study of the effect of immune signal on cellular behavior, some researchers have determined that inflammatory cytokines have an effect on nerve regeneration, so ADSC, which secretes anti-inflammatory cytokines, has a neurotrophic effect. [44] An evaluation of ADSC auxiliary nerve regeneration in mice has shown that intravenous or marginal cerebral injection of ADSC improves memory impairment in mice. In addition to the migration and differentiation of ADSC into neurons, the mechanisms mainly include the paracrine effects of cytokines or neurotrophic factors secreted by ADSC.…”
Section: Treatment Of Nervous System Diseasesmentioning
confidence: 99%